Birth preparednenss and complications readiness among pregnant women in the Gambia. (2025)
Background: The goal of birth preparedness and complication readiness (BPCR) is to minimize delays in seeking care, facilitate the attendance of skilled professionals during birth, and promote facility deliveries. This study aimed to evaluate the knowledge of BPCR among women in the postpartum ward of the Edwards Francis Small Teaching Hospital (EFSTH) in The Gambia. Methods: This was a cross-sectional study conducted at the EFSTH, the only teaching hospital and tertiary care centre in the Gambia. Data was collected using an interviewer-administered questionnaire from 267 consenting parturients. Data was analyzed using the SPSS version 29. Results: The mean age of the participants was 28.6±6.7 years. Of the 220(82.4%) participants who were aware of birth preparedness, 181(67.8%) had a good understanding while one-third, 97(36.3%), demonstrated good knowledge of danger signs in pregnancy. For antenatal care, 117(43.8%), registered during the first trimester, and 219(82%) attended at least four antenatal visits while 168(62.9%) said they had eventful pregnancies. About three-fifths of the participants, 160(59.9%), were adequately prepared for birth and possible challenges although 119(44.6%) made arrangements for the baby's essentials and 201(75.3%) made adequate arrangements for transportation. Statistical analysis revealed significant associations between education level (p=0.01) as well as income (p=0.007) and BPCR. Additionally, gestational age at booking and attendance of skilled personnel during antenatal care (ANC) were significantly associated with knowledge of danger signs in pregnancy (p=0.017 and p=0.015, respectively). Conclusion: Despite meeting the BPCR indicators to some extent based on WHO standards, this study demonstrated existence of gaps in the knowledge and practice of BPCR among pregnant women. Furthermore, socio-economic factors, maternal knowledge, and health services were found to influence BPCR practices. It is therefore important to enhance awareness campaigns, improve pregnant women's understanding of benefits of BPCR, and encourage their partners to adopt shared decision-making options for obstetric services